The Promise of Intranasal Oxytocin in Treating Borderline Personality Disorder: A Narrative Review - Eleni Giannoulis; Christos Nousis; Lydia-Angeliki Eytaxia; Olga Kaimakami; Ioannis Malogiannis (Brain Sciences, 2025)
Background/Objectives: Borderline personality disorder (BPD) is a complex psychiatric condition marked by emotional dysregulation, interpersonal instability, and impulsivity. Despite the advances in psychotherapy and pharmacotherapy, many patients show a partial or unstable response. Recent research suggests that oxytocin, a neuropeptide involved in social cognition and emotional regulation, may offer novel therapeutic avenues. Methods: We systematically synthesize evidence from PubMed, PsycINFO, Web of Science, and Google Scholar on oxytocin’s role in BPD, prioritizing studies on neurobiology, emotion regulation, clinical interventions, and adjunctive therapy models. Thirty studies were included and critically appraised using PRISMA and Cochrane’s tools. Due to methodological heterogeneity, no meta-analysis was conducted; instead, the findings were integrated through a narrative synthesis approach. Results: Evidence supports oxytocin’s modulatory effects on amygdala reactivity, prefrontal–limbic connectivity, and hypothalamic–pituitary–adrenal axis function. Intranasal oxytocin appears beneficial for emotional regulation and interpersonal sensitivity, particularly in individuals with early trauma. The reported effect sizes ranged from small (Cohen’s d ≈ 0.40) to large (d ≈ 0.83), though some trials reported null or adverse effects, such as increased hypermentalization. Heterogeneous responses were influenced by factors such as sex, trauma history, and OXTR gene variants. Conclusions: Although intranasal oxytocin shows promise in modulating core neurobiological systems implicated in BPD and enhancing emotion regulation and social cognition, its clinical effects remain variable and context-dependent. The evidence supports cautious exploration of oxytocin as an adjunct to psychotherapeutic interventions rather than as a standalone treatment. Future research should focus on biomarker-informed, stratified trials that account for trauma history, genetic variation, and sex differences to clarify its therapeutic potential.